2010
DOI: 10.1016/j.rbmo.2010.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Family planning, fertility awareness and knowledge about Italian legislation on assisted reproduction among Italian academic students

Abstract: Over the last century, most industrialized countries have experienced a progressive increase in maternal age at first pregnancy and a reduction of fertility rate, with important social and economic consequences. Moreover in Italy a very restrictive law on assisted reproductive technologies was introduced in 2004, limiting its effectiveness and causing a strong public debate that unfortunately focused more on the political and ethical implications of the law than on the medical and technical aspects of assisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
56
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 19 publications
14
56
1
5
Order By: Relevance
“…Previous studies reported knowledge gaps concerning fertility awareness, parenting attitudes, and specific factors influencing fertility in students in Europe [10][11][12][13][14][15][16][17], Asia [18][19][20], Africa [21], Australia [22,23], Canada [24,25], and the USA [26,27]. These studies have investigated the knowledge of young people or students, but little is known about the attitude of students towards ART and oocyte freezing as well as the differences in knowledge about fertility in special groups, e.g., medical and non-medical students and between sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported knowledge gaps concerning fertility awareness, parenting attitudes, and specific factors influencing fertility in students in Europe [10][11][12][13][14][15][16][17], Asia [18][19][20], Africa [21], Australia [22,23], Canada [24,25], and the USA [26,27]. These studies have investigated the knowledge of young people or students, but little is known about the attitude of students towards ART and oocyte freezing as well as the differences in knowledge about fertility in special groups, e.g., medical and non-medical students and between sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Men and women are not sufficiently aware about age and fertility, and they overestimate the success rate of assisted reproduction techniques (Lampic et al , 2006; Skoog Svanberg et al , 2006). Knowledge gaps about fertility issues have also been found among US, Finnish, Italian, Israeli and Canadian university students (Bretherick et al ., 2010; Rovei et al ., 2010; Hashiloni-Dolev et al ., 2011; Virtala et al ., 2011; Peterson et al , 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Fontos ugyanakkor felismernünk azt, hogy bár az orvostanhallgatók nagy számban találkoztak a meddőség jelenségével (48%), ennek ellenére azok sem rendelkeznek minden esetben helytálló ismeretekkel, akik szemé-lyesen ismernek termékenységi gondokkal küzdő páro-kat, hiszen a helyes defi níciót alkotók aránya 35% volt. Az előzetes szakirodalmi adatokat [11,12,13,14,15,16] alátámasztva tehát a vizsgálatunk is homályos téma-specifi kus ismeretekre derített fényt az orvostanhallgatók körében. Vizsgálatunkban a meddőségi diagnózishoz szüksé-ges időt a kitöltők átlagosan a szakirodalmi adatokkal egybevágóan becsülték meg, azonban a válaszok 6 hó-nap és 10 év között ingadoztak, ami nagyon hasonlít az Okonofua, Harris és Odebiyi [21] által leírtakhoz.…”
Section: Megbeszélésunclassified
“…Az ál-taluk megkérdezettek a diagnózishoz szükséges időt 5 hónap és 5 év közötti intervallum között becsülték. Mindez jól példázza azt, hogy még a jövőbeli egészség-ügyi szakemberek között is mennyire változatos formát öltenek a meddőséghez fűződő elképzelések, ahogyan arra már mások is rámutattak laikusok körében [11,12,13,14,16].…”
Section: Megbeszélésunclassified
See 1 more Smart Citation